The role of jaboticaba (Plinia jaboticaba (VELL.) Berg) phenolic compounds in obesity-associated intestinal inflammation - Rodrigues, Larissa (2021)
Jaboticaba (Plinia jaboticaba (Vell.) Berg) is a Brazilian native fruit belonging to the Myrtaceae family. Previously it was demonstrated that phenolicrich extracts from jaboticaba (PEJ) possess health-beneficial properties in dietinduced obesity; however, whether PEJ modulates the obesity-associated intestinal inflammatory status remains unclear. The objective of the present study was to evaluate the effect of PEJ on intestinal inflammation associated with obesity induced by a high-fat-sucrose (HFS) diet. Thus, forty male C57BL/6J mice were distributed into two groups: negative control (CH, 10 animals), fed standard diet AIN96M and water ad libitum; and positive control (HFS, 30 animals), fed HFS diet and water ad libitum induced to obesity for an initial period of 14 weeks. After this period, the HFS group was redistributed in three groups of 10 animals each, and continuously fed HFS diet for another 14 weeks: HFS group received daily gavages of water, PEJ1 group received PEJ at the dose of 50 mg of gallic acid equivalent (GAE)/kg body weight (BW and PEJ2 group received PEJ at the dose of 100 mg GAE/kg BW. Feed intake and body mass were monitored weekly, and fasting glucose biweekly. The initial period of obesity-induction demonstrated that the HFS diet was efficient to promote a significant body weight gain and fasting hyperglycemia when compared to the negative control group (CH). At the end of the experiment the animals were euthanized under anesthesia and their organs and tissues were collected. The major classes of phenolic compounds found in PEJ were ellagitannins, anthocyanins including cyanidin and delphinidin glycosides, proanthocyanidins, and free ellagic acid. PEJ-treated animals presented a reduced body weight gain, adiposity and demonstrated significant reversion of insulin resistance and dyslipidemia. In addition, the inflammatory profile of colon demonstrated that PEJ prevented metabolic endotoxemia linked to an attenuation of the HFS diet-induced intestinal inflammation via downregulation of pro-inflammatory mediators such as tumor necrosis factor (TNF-β), membrane transporter toll-like receptor-4 (TLR-4) and nuclear factor-κB (NF-κB) in the colon. These anti-inflammatory effects appear to be involved, at least in part, with an inhibition of the colonic inflammasome pathway of obese mice. Collectively, our data reveals that PEJ exerts a direct anti-inflammatory effect in obesity-associated intestinal inflammation and this outcome is linked to an amelioration of metabolic endotoxemia in obese mice.